Efektivitas Antikonvulsan Glodokan Tiang (Polyathia longifolia) pada Hewan Uji Mencit yang Diinduksi Strikinin - Haryanto Haryanto; Nur Fadila Rustam; Nur Amalinda; Hardianti Hardianti; Fitrinaya Fitrinaya; Nur Halisah (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Epilepsy is a chronic neurological disorder characterized by recurrent seizures due to abnormal electrical activity in the brain. This condition can significantly impact the quality of life of sufferers, making the development of effective and safe anticonvulsant therapies a priority in pharmacological research. This study aimed to evaluate the effectiveness of various anticonvulsant drugs, including herbal candidates, in a mouse model (Mus musculus) using acute and subchronic test protocols. Seizures were induced by administering strychnine, a glycine receptor antagonist that triggers excessive neuronal excitability. Parameters observed included seizure onset (the time from strychnine administration to the onset of the first seizure) and deadtime (the time of survival after a seizure). The study involved six treatment groups: a negative control (Na-CMC), four conventional drug groups (phenytoin, diazepam, pregabalin, and gabapentin), and one herbal candidate group made from Polyalthia longifolia (glodokan tiang). The results showed that most treatment groups were able to delay seizure onset and significantly prolong deadtime compared to the negative control. Statistical analysis using ANOVA yielded a p-value <0.05, indicating a significant difference between groups. The herbal candidate Polyalthia longifolia showed promising anticonvulsant potential, although it did not fully match the effectiveness of conventional drugs such as phenytoin or diazepam. The negative control (Na-CMC) showed the fastest onset and shortest survival time, reflecting the absence of a protective effect against seizures. This study emphasizes the importance of further testing using chronic protocols and evaluating additional parameters such as plasma drug concentrations and neurological side effect profiles. The obtained data are expected to form the basis for the development of anticonvulsant therapies based on a combination of modern drugs and natural ingredients, with the hope of producing safer, more effective treatment alternatives, and potentially reducing dependence on long-term synthetic drugs.